Colloid, porous carbon and preparation method and application thereof

By extracting colloids with high content of pyrrole nitrogen using aromatic-rich hydrocarbon oil, the problem of complex components of porous carbon precursors is solved, and the conductivity and structural optimization of porous carbon is achieved, reducing costs.

CN119430178APending Publication Date: 2025-02-14NINGBO SHANSHAN SILICON-BASED MATERIALS CO LTD

Patent Information

Application Number
CN202411834801.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the porous carbon precursor components are complex, resulting in limited improvement in conductivity.

Method used

Porous carbon is prepared by extracting the gum with aromatic-rich hydrocarbon oil and using gum with high content of pyrrole nitrogen. Combined with carbonization and crushing treatment, the pore structure and conductivity of the porous carbon are optimized.

Benefits of technology

The excellent conductivity of porous carbon is achieved, the specific surface area and pore capacity are improved, and the raw material cost is reduced and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430178A_ABST
    Figure CN119430178A_ABST
Patent Text Reader

Abstract

The invention discloses colloid, porous carbon and a preparation method and application thereof. The preparation method of the colloid comprises the following steps: S1, extracting aromatic hydrocarbon-rich oil by adopting a first solvent to obtain a soluble component which is a component A; wherein the first solvent is selected from one or more of o-dichlorobenzene, dipropyl ether and 3-pentanone; s2, the component A is adsorbed to an aluminum oxide chromatographic column, petroleum ether or n-heptane, methylbenzene and a second solvent are sequentially adopted to wash the chromatographic column, then desorbed matter is obtained, and the second solvent is a mixture of methylbenzene and ethyl alcohol. The colloidal pyrrole is high in nitrogen content, and the porous carbon prepared from the colloidal pyrrole is excellent in conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to colloid, porous carbon and a preparation method and application thereof. Background Art

[0002] With the rapid development of electric vehicles and renewable energy, the demand for high-performance lithium-ion batteries continues to increase. For the negative electrode, the currently widely used negative electrode materials are various carbon materials based on graphite, with a theoretical capacity of only 372mAh / g. In actual application, it is close to the theoretical capacity, and it is difficult to meet higher capacity requirements. Therefore, the research on high-specific-capacity negative electrode active materials has become a general trend. Among them, the theoretical capacity of silicon materials is much higher than that of graphite carbon materials, reaching 4200mAh / g, and the resources are relatively abundant, making it the main choice for the next generation of new negative electrode materials.

[0003] However, the silicon-carbon negative electrode has a serious expansion problem. The volume expansion of silicon material during the charge and discharge process is close to 300%, which will cause a significant decrease in the overall performance of the battery. Faced with the challenges of capacity attenuation and poor cycle stability, solving this defect of silicon material is a research topic at home and abroad. CVD (chemical vapor deposition) deposition of silicon-carbon has been a technical direction with high attention and good performance in recent years.

[0004] Porous carbon materials have advantages such as high specific surface area, excellent conductivity and good mechanical stability. They are also key materials for CVD deposition of silicon carbon and must have high performance and feasibility for large-scale production.

[0005] Porous carbon materials can usually be prepared from cheap natural resources, which helps to reduce the cost of battery manufacturing, thereby achieving sustainable development while reducing dependence on limited resources.

[0006] With the widespread application of porous carbon in silicon-carbon anodes, many research institutions and companies have begun to promote its industrialization. The development of this field is not only of great significance to the advancement of battery technology, but also helps to promote the development of renewable energy and electric transportation. The combination of porous carbon and silicon-carbon anode opens up new possibilities for higher performance and more sustainable lithium-ion batteries, and will play a key role in the future energy storage field.

[0007] Porous carbon materials have high specific surface area, good electrical conductivity and good mechanical stability. They are ideal materials for improving defects in silicon-carbon anodes and are widely used in the manufacture of CVD silicon anodes. The pore size, specific surface area and pore volume of porous carbon have an important influence on the structure and performance of CVD silicon anodes.

[0008] In the CVD process, porous carbon, as a substrate material, is a good carrier for silicon nucleation and growth. Its developed pore structure is conducive to expanding the specific surface area of ​​the silicon negative electrode, thereby improving the electrochemical activity of the electrode. At the same time, the conductivity and thermal stability of porous carbon are directly related to the overall performance of the silicon negative electrode.

[0009] There are many methods for producing porous carbon, such as template method, activation method, etc. The activation method mainly uses chemical reagents to react with carbon precursors under high temperature conditions to achieve the purpose of pore formation. Commonly used activation reagents include KOH, KHCO3, NaHCO3, H3PO4 and ZnCl2. In recent years, researchers have been continuously studying new preparation methods to improve the performance of porous carbon and reduce costs. For example, by adjusting the pore size and morphology of the template, optimizing the activation conditions and other means, the directional preparation of porous carbon can be achieved. These studies provide strong support for the application of porous carbon in the field of CVD silicon anode.

[0010] The silicon itself in CVD silicon carbon is not conductive and is an insulator, and the construction of a conductive network mainly relies on a porous carbon skeleton and a conductive coating formed by depositing conductive substances (carbon, gold, silver, copper, aluminum, iron, etc.). As in patent CN202311507560.1, improving conductivity basically relies on the existing carbon skeleton conductivity + carbon deposition layer. There are also methods for improving the carbon skeleton with heteroatoms, such as patent CN202311439082.5. Even if some methods use asphalt as a raw material to prepare porous carbon, such as patent CN202310054027.8, they do not pay enough attention to the effect of the component composition of the asphalt itself on the conductivity of porous carbon, and they cannot further improve the conductivity of porous carbon while maintaining the performance of porous carbon. Therefore, it is necessary to pay attention to the effect of the component composition of the porous carbon precursor on the performance of the porous carbon skeleton.

[0011] The method to improve the conductivity of porous carbon skeletons is to dope and modify the carbon skeleton materials, such as doping with heteroatoms such as N / S, or doping with metal atoms such as Au / Ag / Al / Cu / Fe on the carbon skeleton, or using a conductive deposition layer. If the pores are too rich, the porous carbon skeleton material will be too brittle, the carbon wall will be thin, and the conductivity will be poor, which will increase the resistance of silicon carbon to a certain extent. Therefore, it is necessary to find a suitable balance between pore structure and conductivity. Therefore, it is necessary to study the direction of different conductivity of porous carbon caused by the difference in the proportion of components in the porous carbon precursor, especially focusing on the difference in the components of the porous carbon precursor and the effect on conductivity.

[0012] Regarding the improvement of the conductivity of porous carbon, the current related improvement research can be divided into several situations:

[0013] 1. Either the asphalt components are not separated and distinguished, such as patent CN115818638A, which uses all the asphalt components as carbon sources for carbonization without distinguishing the impact of the components on performance;

[0014] 2. Either additional nitrogen source is introduced during the carbonization process for doping, and in-situ carbonization is performed together with the carbon source, such as patent CN111302326A and patent CN111484013A;

[0015] 3. Either the components are separated and cut, and nitrogen doping is performed, but the nitrogen source is still introduced from the outside. However, the structure of the doped nitrogen to improve the conductivity has not been regulated, and the proportion of nitrogen doping site types is unclear. The doping effect can only be inferred through subsequent application performance. For example, patent CN116721877A has done component separation, but still introduced an external nitrogen source for doping.

[0016] Aromatic-rich oil refers to a resource rich in C7 and above aromatics, and is used as one of the raw materials for preparing asphalt. The prior art has not reported the direct extraction of colloid using aromatic-rich oil, and the prior art mostly uses asphalt as a raw material to extract colloid. Summary of the invention

[0017] The technical problem to be solved by the present invention is to overcome the defects of the prior art that the porous carbon precursor components are complex and the degree of improvement of the conductivity of the porous carbon is limited, and to provide a colloid, porous carbon and a preparation method and application thereof. The colloid of the present invention has a high pyrrole nitrogen content, and the porous carbon prepared therefrom has excellent conductivity.

[0018] The present invention adopts the following technical solutions to solve the above technical problems.

[0019] The present invention provides a method for preparing a colloid, which comprises the following steps:

[0020] S1. Extracting the aromatic-rich oil with a first solvent to obtain a soluble component as component A; wherein the first solvent is selected from one or more of o-dichlorobenzene, dipropyl ether and 3-pentanone;

[0021] S2. Adsorbing the component A onto an alumina chromatographic column, and eluting the chromatographic column with petroleum ether or n-heptane, toluene, and a second solvent in sequence to obtain a desorbed product, wherein the second solvent is a mixture of toluene and ethanol.

[0022] In the present invention, preferably, the mass percentage of pyrrole nitrogen in the colloid is 60%-75%, such as 61.3%, 68.8%, 69.5% or 74.3%.

[0023] In the present invention, preferably, the mass percentage of pyridinic nitrogen in the colloid is 14%-21%, such as 14.4%, 14.7%, 17.6% or 20.3%.

[0024] In the present invention, preferably, the mass percentage of amino nitrogen in the colloid is 8%-20%, such as 8.1%, 15.8%, 16.8% or 18.4%.

[0025] In the present invention, the colloid is generally in the state of viscous liquid.

[0026] In step S1 of the present invention, the amount of the first solvent may be a conventional amount in the art. Preferably, during the extraction, the mass-to-volume ratio of the mass of the aromatic-rich oil to the volume of the first solvent is 1 g:(8-12) mL, for example, 1 g:10 mL.

[0027] In step S1 of the present invention, the temperature during the extraction may be the extraction temperature in the art, preferably, the temperature during the extraction is 75-85°C, for example, 80°C.

[0028] In step S1 of the present invention, the extraction time may be the extraction time in the art, preferably, the extraction time is 50-70 min, for example, 60 min.

[0029] In step S1 of the present invention, the extraction step further includes the following steps: filtering to obtain a filtrate, and further removing the first solvent to obtain component A.

[0030] In the present invention, the aromatics-rich oil generally includes four components: saturates, aromatics, colloids and asphaltenes.

[0031] In the present invention, preferably, the mass percentage of aromatics in the aromatics-rich oil is greater than 50%.

[0032] In the present invention, preferably, the aromatics-rich oil is selected from one or more of catalytic gasoline, cracking gasoline, catalytic diesel, catalytic reforming aromatics, ethylene cracking tar, ethylene tar, catalytic cracking slurry, medium and low temperature coal tar and bio-tar.

[0033] In the present invention, preferably, the softening point (SP) of the aromatics-rich oil is 0-40°C, for example, 25°C.

[0034] In the present invention, the component A generally includes saturated fractions, aromatic fractions and gum.

[0035] In the present invention, the petroleum ether is, for example, petroleum ether with a boiling point of 60-90°C.

[0036] In the present invention, after the petroleum ether is used to elute the chromatographic column, the desorbed products generally include saturated fractions, and the adsorbed products retained on the chromatographic column generally include aromatic fractions and colloids.

[0037] In the present invention, after further eluting the chromatographic column with the toluene, the desorbed product generally includes aromatic components, and the adsorbed product retained on the chromatographic column generally includes colloids. Finally, after eluting with the second solvent, the desorbed product generally includes the colloids.

[0038] In the present invention, preferably, the volume ratio of toluene to ethanol in the second solvent is 1:(0.8-1.2), for example, 1:1.

[0039] The present invention also provides a colloid, which is prepared by the colloid preparation method as described above.

[0040] The present invention also provides a method for preparing porous carbon, which comprises the following steps:

[0041] The colloid described in any one of the present invention and the pore-forming agent are mixed, and then carbonized and crushed in sequence.

[0042] In the present invention, preferably, the specific surface area of ​​the porous carbon is 700-1900m 2 / g, for example, 795m 2 / g、899m 2 / g、926m 2 / g、1043m 2 / g, 1182m 2 / g、1623m 2 / g, 1641m 2 / g or 1897m 2 / g.

[0043] In the present invention, preferably, the average pore diameter of the porous carbon is 3-15 nm, for example, 3.109 nm, 3.209 nm, 3.278 nm, 4.641 nm, 5.017 nm, 5.176 nm, 12.76 nm or 14.45 nm.

[0044] In the present invention, preferably, the pore volume of the porous carbon is 0.5-1.5 cm 3 / g, for example, 0.5436cm 3 / g, 0.7078cm 3 / g, 0.7497cm 3 / g, 0.8387cm 3 / g, 0.9402cm 3 / g, 0.9423cm 3 / g, 0.9654cm 3 / g or 1.4936cm 3 / g.

[0045] In the present invention, preferably, at 30 MPa, the powder resistivity of the porous carbon is 0.05-0.09 Ω·cm, for example, 0.0547 Ω·cm, 0.0589 Ω·cm, 0.0615 Ω·cm, 0.0653 Ω·cm, 0.0721 Ω·cm, 0.0778 Ω·cm, 0.0876 Ω·cm or 0.0918 Ω·cm.

[0046] In the present invention, preferably, the mixing time is 0.1-2 h, more preferably 0.2-2 h, further more preferably 0.5-1.5 h, for example 30 min.

[0047] In the present invention, preferably, the temperature during the mixing is 70-90°C, for example, 80°C.

[0048] In the present invention, preferably, the mass ratio of the colloid to the pore-forming agent is 1:(1-10), more preferably 1:(1.5-6), and further preferably 1:(2-5), for example 1:1, 1:1.5 or 1:10.

[0049] In the present invention, the pore-forming agent may be a conventional pore-forming agent. Preferably, the pore-forming agent is selected from one or more of potassium carbonate, potassium chloride and potassium hydroxide.

[0050] In the present invention, preferably, the pore-forming agent is potassium carbonate and potassium chloride, and the mass ratio of potassium carbonate to potassium chloride is 1:1.

[0051] In the present invention, preferably, an inert gas is introduced before the carbonization.

[0052] The inert gas is, for example, nitrogen.

[0053] Preferably, the speed of introducing the inert gas is 0.15-0.25 L / min, for example, 0.2 L / min.

[0054] In the present invention, preferably, the carbonization includes low-temperature carbonization and high-temperature carbonization. Wherein, the low-temperature carbonization satisfies one or more of the following conditions:

[0055] a. The low temperature carbonization temperature is 250-500 ℃;

[0056] b. The heating rate of heating to the low temperature carbonization temperature is 1-20 ° C / min;

[0057] c. The constant temperature time of the low temperature carbonization is 1-8h;

[0058] The high temperature carbonization satisfies one or more of the following conditions:

[0059] a. The high temperature carbonization temperature is 500-1400 ℃;

[0060] b. The heating rate of heating to the high temperature carbonization temperature is 1-20 ° C / min;

[0061] c. The constant temperature time of the high temperature carbonization is 1-8h.

[0062] Preferably, the low temperature carbonization satisfies one or more of the following conditions:

[0063] a. The low temperature carbonization temperature is 280-480 ℃;

[0064] b. The heating rate of heating to the low temperature carbonization temperature is 1-15°C / min;

[0065] c. The constant temperature time of the low temperature carbonization is 1-6h;

[0066] More preferably, the low temperature carbonization satisfies one or more of the following conditions:

[0067] a. The low temperature carbonization temperature is 320-460 ℃;

[0068] b. The heating rate of heating to the low temperature carbonization temperature is 1-12 ° C / min;

[0069] c. The constant temperature time of the low temperature carbonization is 1.5-6h;

[0070] For example, the low temperature carbonization satisfies one or more of the following conditions:

[0071] a. The low temperature carbonization temperature is 450 ℃;

[0072] b. The heating rate of heating to the low temperature carbonization temperature is 1 ° C / min;

[0073] c. The constant temperature time of the low temperature carbonization is 3h.

[0074] Preferably, an inert gas atmosphere is maintained during the high-temperature carbonization, for example, the inert gas is introduced.

[0075] The inert gas is, for example, nitrogen.

[0076] Preferably, the speed of introducing the inert gas is 0.1-0.25 L / min, for example, 0.15 L / min.

[0077] Preferably, the high temperature carbonization satisfies one or more of the following conditions:

[0078] a. The high temperature carbonization temperature is 600-1300 ℃;

[0079] b. The heating rate of heating to the high temperature carbonization temperature is 2-15 ° C / min;

[0080] c. The constant temperature time of high temperature carbonization is 2-6h;

[0081] More preferably, the high temperature carbonization satisfies one or more of the following conditions:

[0082] a. The high temperature carbonization temperature is 700-1200 ℃;

[0083] b. The heating rate of heating to the high temperature carbonization temperature is 3-12 ° C / min;

[0084] c. The constant temperature time of high temperature carbonization is 3-6h;

[0085] For example, the high temperature carbonization satisfies one or more of the following conditions:

[0086] a. The high temperature carbonization temperature is 1000 ℃;

[0087] b. The heating rate is 5°C / min to the high temperature carbonization temperature;

[0088] c. The constant temperature time of the high temperature carbonization is 4h.

[0089] Preferably, after the high-temperature carbonization, the processes of cooling, pickling, water washing and drying are sequentially included.

[0090] The cooling is, for example, cooling to room temperature.

[0091] The number of times of pickling can be conventional in the art, for example, 3 times.

[0092] The number of times of water washing can be conventional in the art, for example, 3 times.

[0093] In the present invention, preferably, the average pore size of the porous carbon after the crushing treatment is 3-15 nm, for example, 3.109 nm, 3.209 nm, 3.278 nm, 4.641 nm, 5.017 nm, 5.176 nm, 12.76 nm or 14.45 nm.

[0094] The present invention also provides a porous carbon, which is prepared by the method for preparing the porous carbon as described above.

[0095] The present invention also provides an application of the porous carbon as described above in a silicon-carbon composite material or as a pole piece material.

[0096] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0097] The reagents and raw materials used in the present invention are commercially available.

[0098] The positive and progressive effects of the present invention are:

[0099] The colloid extracted from the aromatic-rich oil is rich in pyrrole nitrogen, with a pyrrole nitrogen content of not less than 61%. The porous carbon prepared from the colloid has excellent electrical conductivity.

[0100] The raw material for extracting colloid in the present invention is aromatic-rich oil, and there is no need to prepare the aromatic-rich oil into asphalt for further extraction, so the preparation method is simple.

[0101] The porous carbon of the present invention adopts colloid extracted from aromatic-rich oil as raw material. The colloid is rich in pyrrole nitrogen, and no external nitrogen source needs to be introduced, thereby streamlining raw materials and reducing raw material costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0102] Figure 1 Flow chart of the method for preparing the colloid in Example 1. DETAILED DESCRIPTION

[0103] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0104] The main raw material information involved in the examples and comparative examples of the present invention is shown in the following table:

[0105]

[0106] Example 1

[0107] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is as follows:

[0108] S1. Preparation method of colloid. The flow chart of the preparation method of colloid is as follows Figure 1As shown. Weigh 40g of the raw material liquid rich aromatic oil (SP is 25℃) and 400mL of o-dichlorobenzene into a stainless steel reactor at normal pressure, heat to 80℃, stir for 60min, and filter while hot to obtain o-dichlorobenzene solubles. Distill the o-dichlorobenzene solution to obtain component A, which includes saturated fractions, aromatic fractions and gums; then adsorb component A on an alumina chromatographic column and elute with 250ml of high boiling range petroleum ether (60-90℃), toluene, and toluene-ethanol (the volume ratio of toluene to ethanol is 1:1). Among them, the desorbent obtained after eluting the chromatographic column with petroleum ether is component B, which includes saturated fractions, and the adsorbent retained on the chromatographic column includes aromatic fractions and gums; the desorbent obtained after eluting the chromatographic column with toluene is component C, which includes aromatic fractions, and the adsorbent retained on the chromatographic column includes gums; the desorbent obtained after eluting the chromatographic column with toluene-ethanol is component D, which includes gums.

[0109] Among them, aromatics-rich oil includes four components: saturates, aromatics, colloids and asphaltenes.

[0110] S2, impregnation and mixing. Add 10 g of component D of the viscous liquid obtained in step S1 and 20 g of a mixed pore-forming agent of potassium carbonate and potassium chloride (the mass ratio of potassium carbonate to potassium chloride is 1:1) into a 100 mL beaker, and stir and mix in a liquid phase at 80° C. for 30 min.

[0111] S3, low temperature carbonization. The mixed liquid phase material is transferred to a quartz crucible boat, and placed in a tube furnace, and N2 is introduced at a gas rate of 0.2L / min. The temperature is continued to rise to 450℃ at a rate of 1℃ / min and kept constant for 3h to fully gasify the volatile matter;

[0112] S4, high temperature carbonization. Maintain nitrogen atmosphere, gas velocity is 0.15L / min, continue to heat the material after low temperature carbonization to 1000℃ at a heating rate of 5℃ / min and keep the temperature constant for 4h, cool to room temperature, take out, pickle 3 times, wash 3 times with water and then dry;

[0113] S5, crushing treatment. The material obtained in step S4 is crushed to obtain a porous carbon material.

[0114] Example 2

[0115] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of embodiment 1 only in that "o-dichlorobenzene" in step S1 is replaced by "dipropyl ether". The remaining conditions and parameters are the same as those of embodiment 1.

[0116] Example 3

[0117] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of embodiment 1 only in that "o-dichlorobenzene" in step S1 is replaced by "3-pentanone". The remaining conditions and parameters are the same as those of embodiment 1.

[0118] Example 4

[0119] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of Embodiment 1 only in that the mass ratio of component D to the mixed pore-forming agent in step S2 is different, and the mass ratio of component D to the mixed pore-forming agent in step S2 of this embodiment is 1:1.5. The other conditions and parameters are the same as those of Embodiment 1.

[0120] Example 5

[0121] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of Embodiment 1 only in that the mass ratio of component D to the mixed pore-forming agent in step S2 is different, and the mass ratio of component D to the mixed pore-forming agent in step S2 of this embodiment is 1:10. The other conditions and parameters are the same as those of Embodiment 1.

[0122] Example 6

[0123] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of embodiment 1 only in that the temperature and time of high temperature carbonization in step S4 are different, and in step S4 of this embodiment, the temperature is continuously raised to 700° C. and kept constant for 2 hours. The other conditions and parameters are the same as those of embodiment 1.

[0124] Example 7

[0125] This embodiment provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of embodiment 1 only in that the temperature and time of high temperature carbonization in step S4 are different, and in step S4 of this embodiment, the temperature is continuously raised to 1300° C. and kept constant for 5.5 hours. The other conditions and parameters are the same as those of embodiment 1.

[0126] Example 8

[0127] This comparative example provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of Example 1 only in that the "petroleum ether" in Example 1 is replaced by "n-heptane", and the other conditions and parameters are the same as those in Example 1.

[0128] Comparative Example 1

[0129] This comparative example provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of Example 1 only in that the aromatics-rich oil in step S1 is not extracted with o-dichlorobenzene. The other conditions and parameters are the same as those of Example 1.

[0130] Comparative Example 2

[0131] This comparative example provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of Example 1 only in that after the petroleum ether is extracted in step S1, toluene and toluene+ethanol are not further used for desorption separation. The remaining conditions and parameters are the same as those of Example 1.

[0132] Comparative Example 3

[0133] This comparative example provides a colloid and a porous carbon prepared from the colloid, and the preparation method thereof is different from that of Example 1 only in that: in step S1, the aromatics-rich oil is first adsorbed on an alumina chromatographic column, and then eluted with petroleum ether, toluene, and toluene-ethanol in sequence to obtain a desorbed component, and then the desorbed component is extracted with o-dichlorobenzene. The remaining conditions and parameters are the same as those of Example 1.

[0134] Comparative Example 4

[0135] This comparative example provides a colloid and porous carbon prepared from the colloid, and the preparation method thereof is different from that of Example 1 only in that "o-dichlorobenzene" in Example 1 is replaced by "n-heptane", and the other conditions and parameters are the same as those in Example 1.

[0136] Effect Example 1

[0137] (1) Determination of total nitrogen yield

[0138] The contents of C, H, N and S in the samples were determined using a German Vario ELcube element analyzer.

[0139] (2) Determination of the mass percentage of pyrrolic nitrogen, pyridinic nitrogen and amino nitrogen in total nitrogen

[0140] XPS analysis of the types, contents and chemical forms of the surface elements of each component of coal tar pitch was performed. The X-ray source was AlKα monochromator with a power of 150 W. The energy analyzer used CAE mode, and the internal standard was 284.8 eV (C1s).

[0141] The total nitrogen yield of component D (colloid) obtained in Examples 1-8 and Comparative Examples 1-4, the mass percentages of pyrrole nitrogen, pyridinic nitrogen and amino nitrogen in the total nitrogen, and the mass percentages of pyrrole nitrogen, pyridinic nitrogen and amino nitrogen in the porous carbon obtained in Examples 1-8 and Comparative Examples 1-4 are shown in Table 1.

[0142] Table 1

[0143]

[0144] It can be seen from Table 1 that the content of pyrrole nitrogen in component D (colloid) obtained in Examples 1-8 is higher than that in Comparative Examples 1-4; the content of pyrrole nitrogen in the porous carbon obtained in Examples 1-8 is also higher than that in Comparative Examples 1-4.

[0145] It can be seen from Table 1 that the proportions of pyrrolic nitrogen, pyridinic nitrogen and amino nitrogen in the porous carbon obtained after carbonization are not the same as those in the colloid. This is because part of the pyrrolic nitrogen is converted into pyridinic nitrogen after carbonization, while the amino nitrogen may be related to the length of the colloid side chain and is easily converted into pyrrolic nitrogen and pyridinic nitrogen by bond breaking during the subsequent carbonization process at a temperature of more than 500°C.

[0146] Effect Example 2

[0147] (1) Porous carbon test characterization

[0148] The ASAP2020 specific surface area adsorption instrument was used to determine the specific surface area, pore volume and pore size of the porous carbon by N2 adsorption method.

[0149] (2) Resistivity measurement of porous carbon powder

[0150] The test was conducted using a FDM-1650 four-probe powder resistance tester. Test parameters: experimental area 132.73mm 2 , sample weight 0.6g, variable pressure mode test, test pressure range: 10-350MPa, pressure step 20MPa, pressure holding time 10s. Test times: each sample is tested twice in parallel.

[0151] The test characterization structures of the porous carbon of Examples 1-8 and Comparative Examples 1-4 are shown in Table 2.

[0152] Table 2

[0153]

[0154] It can be seen from Table 2 that the specific surface area, pore volume and pore diameter of the porous carbon obtained in Examples 1-8 are comparable to those of the porous carbon obtained in Comparative Examples 1-4, and the powder resistivity of the porous carbon obtained in Examples 1-8 is lower than that of the porous carbon obtained in Comparative Examples 1-4, which indicates that the porous carbon of the present invention has better electrical conductivity.

Claims

1. A method for preparing a colloid, characterized in that: It includes the following steps: S1. Extracting the aromatics-rich oil with a first solvent to obtain a soluble component as component A; wherein the first solvent is selected from one or more of o-dichlorobenzene, dipropyl ether and 3-pentanone; S2. Adsorbing the component A onto an alumina chromatographic column, and eluting the chromatographic column with petroleum ether or n-heptane, toluene, and a second solvent in sequence to obtain a desorbed product, wherein the second solvent is a mixture of toluene and ethanol.

2. The method for preparing the colloid as claimed in claim 1, characterized in that: It meets one or more of the following conditions: (1) The mass percentage of pyrrolic nitrogen in the colloid is 60%-75%, such as 61.3%, 68.8%, 69.5% or 74.3%; (2) The mass percentage of pyridinic nitrogen in the colloid is 14%-21%, such as 14.4%, 14.7%, 17.6% or 20.3%; (3) The mass percentage of amino nitrogen in the colloid is 8%-20%, for example, 8.1%, 15.8%, 16.8% or 18.4%.

3. The method for preparing the colloid as claimed in claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S1, during the extraction, the mass-to-volume ratio of the mass of the aromatic-rich oil to the volume of the first solvent is 1 g:(8-12) mL, for example, 1 g:10 mL; (2) In step S1, the temperature during extraction is 75-85°C, for example, 80°C; (3) In step S1, the extraction time is 50-70 minutes, for example, 60 minutes; (4) In step S1, the extraction step further includes the following steps: filtering to obtain a filtrate, and further removing the first solvent to obtain the component A.

4. The method for preparing the colloid as claimed in claim 1, characterized in that: It meets one or more of the following conditions: (1) The aromatics-rich oil includes four components: saturates, aromatics, colloids and asphaltenes; (2) The mass percentage of aromatics in the aromatics-rich oil is greater than 50%; (3) The aromatics-rich oil is selected from one or more of catalytic gasoline, pyrolysis gasoline, catalytic diesel, catalytic reforming aromatics, ethylene cracking tar, ethylene tar, catalytic cracking slurry, medium and low temperature coal tar and bio-tar; (4) The softening point of the aromatics-rich oil is 0-40°C, for example, 25°C; (5) Component A includes saturated components, aromatic components and colloids; (6) The petroleum ether is a petroleum ether with a boiling point of 60-90°C; (7) The volume ratio of toluene to ethanol in the second solvent is 1:(0.8-1.2), for example, 1:

1.

5. A colloid, characterized in that: The colloid is prepared by the colloid preparation method described in any one of claims 1 to 4.

6. A method for preparing porous carbon, characterized in that: It includes the following steps: The colloid as claimed in claim 5 and the pore-forming agent are mixed, and then carbonized and crushed in sequence.

7. The method for preparing porous carbon according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The specific surface area of ​​the porous carbon is 700-1900m 2 / g, for example, 795m 2 / g、899m 2 / g、926m 2 / g、1043m 2 / g, 1182m 2 / g、1623m 2 / g, 1641m 2 / g or 1897m 2 / g; (2) The average pore size of the porous carbon is 3-15 nm, for example, 3.109 nm, 3.209 nm, 3.278 nm, 4.641 nm, 5.017 nm, 5.176 nm, 12.76 nm or 14.45 nm; (3) The pore volume of the porous carbon is 0.5-1.5 cm 3 / g, for example, 0.5436cm 3 / g, 0.7078cm 3 / g, 0.7497cm 3 / g, 0.8387cm 3 / g, 0.9402cm 3 / g, 0.9423cm 3 / g, 0.9654cm 3 / g or 1.4936cm 3 / g; (4) At 30 MPa, the powder resistivity of the porous carbon is 0.05-0.09 Ω·cm, for example, 0.0547 Ω·cm, 0.0589 Ω·cm, 0.0615 Ω·cm, 0.0653 Ω·cm, 0.0721 Ω·cm, 0.0778 Ω·cm, 0.0876 Ω·cm or 0.0918 Ω·cm.

8. The method for preparing porous carbon according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The mixing time is 0.1-2h, preferably 0.2-2h, more preferably 0.5-1.5h, for example 30min; (2) The temperature during mixing is 70-90° C., for example, 80° C.; (3) The mass ratio of the colloid to the pore-forming agent is 1:(1-10), preferably 1:(1.5-6), more preferably 1:(2-5), for example 1:1, 1:1.5 or 1:10; (4) The pore-forming agent is selected from one or more of potassium carbonate, potassium chloride and potassium hydroxide; preferably, the pore-forming agent is potassium carbonate and potassium chloride, and the mass ratio of potassium carbonate to potassium chloride is 1:1; (5) before the carbonization, introducing an inert gas; Wherein, the inert gas is, for example, nitrogen; Preferably, the speed of introducing the inert gas is 0.15-0.25 L / min, for example, 0.2 L / min; (6) The carbonization includes low-temperature carbonization and high-temperature carbonization; wherein the low-temperature carbonization satisfies one or more of the following conditions: a. The low temperature carbonization temperature is 250-500 ℃; b. The heating rate of heating to the low temperature carbonization temperature is 1-20 ° C / min; c. The constant temperature time of the low temperature carbonization is 1-8h; The high temperature carbonization satisfies one or more of the following conditions: a. The high temperature carbonization temperature is 500-1400 ℃; b. The heating rate is 1-20°C / min to the high temperature carbonization temperature; c. The constant temperature time of high temperature carbonization is 1-8h; Preferably, the low temperature carbonization satisfies one or more of the following conditions: a. The low temperature carbonization temperature is 280-480 ℃; b. The heating rate of heating to the low temperature carbonization temperature is 1-15°C / min; c. The constant temperature time of the low temperature carbonization is 1-6h; More preferably, the low temperature carbonization satisfies one or more of the following conditions: a. The low temperature carbonization temperature is 320-460 ℃; b. The heating rate of heating to the low temperature carbonization temperature is 1-12 ° C / min; c. The constant temperature time of the low temperature carbonization is 1.5-6h; For example, the low temperature carbonization satisfies one or more of the following conditions: a. The low temperature carbonization temperature is 450 ℃; b. The heating rate of heating to the low temperature carbonization temperature is 1 ° C / min; c. The constant temperature time of the low temperature carbonization is 3h; Preferably, an inert gas atmosphere is maintained during the high-temperature carbonization, for example, the inert gas is introduced; The inert gas is, for example, nitrogen; The speed of introducing the inert gas is preferably 0.1-0.25 L / min, for example 0.15 L / min; Preferably, the high temperature carbonization satisfies one or more of the following conditions: a. The high temperature carbonization temperature is 600-1300 ℃; b. The heating rate of heating to the high temperature carbonization temperature is 2-15 ℃ / min; c. The constant temperature time of high temperature carbonization is 2-6h; More preferably, the high temperature carbonization satisfies one or more of the following conditions: a. The high temperature carbonization temperature is 700-1200 ℃; b. The heating rate of heating to the high temperature carbonization temperature is 3-12 ° C / min; c. The constant temperature time of high temperature carbonization is 3-6h; For example, the high temperature carbonization satisfies one or more of the following conditions: a. The high temperature carbonization temperature is 1000 ℃; b. The heating rate is 5°C / min to the high temperature carbonization temperature; c. The constant temperature time of high temperature carbonization is 4h; Preferably, after the high-temperature carbonization, the processes of cooling, pickling, washing and drying are sequentially included; (7) The average pore size of the porous carbon after the crushing treatment is 3-15 nm, for example, 3.109 nm, 3.209 nm, 3.278 nm, 4.641 nm, 5.017 nm, 5.176 nm, 12.76 nm or 14.45 nm.

9. A porous carbon, characterized in that: The porous carbon is prepared by the method for preparing the porous carbon as described in any one of claims 6 to 8.

10. Use of the porous carbon as claimed in claim 9 in a silicon-carbon composite material or as a pole piece material.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon negative electrode material

    CN116314791A

  • Nitrogen-doped silicon-carbon negative electrode material and preparation method thereof

    CN117410466A

  • Composite carbon-silicon negative electrode material and preparation method thereof

    CN117577801A

Cited By

  • Porous carbon carrier for silicon-oxygen negative electrode of lithium battery and preparation method of porous carbon carrier

    CN120622487A